Twelve-Month Cognitive and Functional Outcomes Following Cardiac Surgery: The DEXACET Trial of Intravenous Acetaminophen Versus Placebo - Khera, Tanvi; Helfand, Jordan; Kelly, Lauren; Mueller, Ariel; Shankar, Puja; Marcantonio, Edward R.; Subramaniam, Balachundhar (Frontiers in Pharmacology, 2022)
Background Delirium, an acute decline in attention and global cognitive dysfunction, occurs frequently following cardiac surgery and has been demonstrated to be significantly associated with cognitive dysfunction and reduced functional ability. In the DEXACET trial, we demonstrated a significant reduction in postoperative in-hospital delirium with intravenous (IV) acetaminophen when compared with placebo. In this analysis we examined whether this protective association also extended to 12-month cognitive and functional outcomes. Methods This study was a prospective, randomized, placebo-controlled, triple-blinded, factorial design trial conducted at BIDMC, approved by the IRB. In this trial, 120 older cardiac surgical patients were randomly assigned to receive either intravenous (IV) acetaminophen or placebo in addition to propofol or dexmedetomidine. Those receiving IV acetaminophen displayed a significant reduction in in-hospital delirium. We collected cognitive, mood and functional outcome data using the Montreal Cognitive Assessment, telephone version (T-MoCA), Geriatric Depression Scale (GDS) and the Basic and Instrumental Activities of Daily Living (ADLs, IADLs) at 1 month and 12 months after surgery. Results Of the 120 enrolled patients in the primary trial, 93 (77.5%) and 83 (69.2%) patients responded to assessments at one month and 12 months, respectively. No statistically significant differences in median T-MoCA scores were observed between acetaminophen and placebo groups at one month (18.0 vs.18.0, p=0.52) or 12 months (19.0 vs.18.0, p=0.62) following surgery. There were similarly no differences in GDS, ADLs or IADLs between treatment groups. Losses to follow-up limited the sample sizes and 10 of the 23 (45%) original study participants who had postoperative delirium were lost to follow up. Conclusions Administration of intravenous acetaminophen was not associated with a difference in long term cognitive or functional status following cardiac surgery. Additional research on long-term outcomes following postoperative delirium with a larger sample size and improved cohort retention strategies will be needed to address this important area.